1985
DOI: 10.1128/aac.27.4.520
|View full text |Cite
|
Sign up to set email alerts
|

Renal disposition of gentamicin, dibekacin, tobramycin, netilmicin, and amikacin in humans

Abstract: The tubular disposition of five aminoglycosides was studied in humans to establish a possible relationship between tubular reabsorption and the nephrotoxicity that has been described in the literature. Thirty-three healthy male volunteers received a continuous intravenous infusion of isotonic saline with inulin, followed 1 h later by inulin plus gentamicin, dibekacin, tobramycin, netilmicin, or amikacin (1 mg/kg per h) or amikacin (4 mg/kg per h) over a period of 2 h. Brain-stem-evoked response audiometry was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…In vivo studies both in animals and in humans aiming to clarify the efficacy of the combination of vancomycin plus rifampin against serious MRSA infections, including endocarditis, also yielded conflicting results (2,4,23,25,38). On the basis of the contradictory information reported elsewhere, the present experimental study was designed in an effort to elucidate the role of netilmicin against MGRSA after considering that MGRSA isolates are often susceptible to netilmicin (16a); that, compared with gentamicin, netilmicin has better pharmacokinetic properties within the vegetation (13); and that netilmicin is less nephrotoxic (11,22,26,31). The present study was also designed to redefine the role of the addition of rifampin to vancomycin or to the combination of vancomycin plus netilmicin and to investigate the influence of the duration of therapy on different therapeutic regimens.…”
Section: Vol 39 1995 Vancomycin Plus Netilmicin For S Aureus Endocmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies both in animals and in humans aiming to clarify the efficacy of the combination of vancomycin plus rifampin against serious MRSA infections, including endocarditis, also yielded conflicting results (2,4,23,25,38). On the basis of the contradictory information reported elsewhere, the present experimental study was designed in an effort to elucidate the role of netilmicin against MGRSA after considering that MGRSA isolates are often susceptible to netilmicin (16a); that, compared with gentamicin, netilmicin has better pharmacokinetic properties within the vegetation (13); and that netilmicin is less nephrotoxic (11,22,26,31). The present study was also designed to redefine the role of the addition of rifampin to vancomycin or to the combination of vancomycin plus netilmicin and to investigate the influence of the duration of therapy on different therapeutic regimens.…”
Section: Vol 39 1995 Vancomycin Plus Netilmicin For S Aureus Endocmentioning
confidence: 99%
“…On the other hand, the therapeutic role of rifampin in MRSA endocarditis is controversial (4), and today the majority of MRSA endocarditis strains are also gentamicin resistant (23). Because netilmicin (i) has been found to be active in vitro against MRSA strains cross resistant to gentamicin (16a), (ii) it possesses decreased nephrotoxic potential in comparison with that of gentamicin (11,22,26,31), and (iii) it has advantageous pharmacokinetics in cardiac valves (13) because of the time that its concentration in the heart valve is greater than the MIC at which 90% of S. aureus strains are inhibited is seven times longer than that of gentamicin (3.5 versus 0.5 h, respectively), we designed the present study in order to compare the therapeutic efficacy of vancomycin, alone or in combination with netilmicin and/or rifampin, in the rabbit model of aortic valve endocarditis caused by a MRSA strain which was also resistant to gentamicin (MGRSA) but which was susceptible to netilmicin. To our knowledge no study evaluating the efficacies of vancomycin and netilmicin as well as the efficacy of the combination with rifampin against MGRSA endocarditis has yet been published.…”
mentioning
confidence: 99%
“…In order to reduce aminoglycoside toxicity, some investigators suggested the use of low doses of gentamicin (30) or other aminoglycosides with lower toxicities, such as netilmicin (4,15). This is the aminoglycoside of choice in our institution, precisely because of its lower toxicity (6,13), and therefore was the aminoglycoside evaluated in the present experimental study. Another way to attenuate aminoglycoside toxicity would be to inject the antibiotic once daily, since this dosing regimen is well tolerated in humans (24,25) and is less ototoxic and nephrotoxic than conventional dosing regimens in animal studies (1, 10, 25, 31).…”
mentioning
confidence: 99%
“…These two antibiotics are not metabolized in humans and are mainly cleared through urinary excretion. They differ in their degrees of binding to serum albumin, i.e., 0% for gentamicin and 82% for cefazolin (6,9). This fact allowed us to study independently the roles of increased vascular permeability and of altered protein binding in the hypothyroid state.…”
mentioning
confidence: 99%